(untitled) (Research, Society and Development, 2020)
The contextualization in the teaching of Botany is fundamental for the promotion of a more meaningful learning. In this sense, the construction of herbarium can be a tool used to relate the syllabus to the student’s daily life. This tool can make students aware of the importance of preserving Brazilian flora and its biodiversity. In this context, this study had as main objective to contextualize the teaching of Botany through the construction of herbarium of medicinal plants. In addition, it was intended to rescue the empirical knowledge about medicinal plants, arouse interest in botany classes and raise students’ awareness of the importance of the conscious use of herbal medicines. The target audience of this research was the 2nd year of high school at the State School Hilda Trautwein Kamal, located in the municipality of Umuarama - PR, Brazil. The students participated in the process of making the herbarium, from choosing the plants that were placed in the paste, to its classification and conducting research on its therapeutic uses. The result of a pre-test (initial diagnosis) shows that the students had no effective knowledge about the medicinal plants used in this study, herbalization or even about the importance of teaching Botany. With the application of contextualized botany classes that resulted in the construction of the herbarium, students obtained greater knowledge on the subject, a fact verified in the evaluation of the results of an applied post-test.